Ex-situ Conservation of Endemic and Threatened Plants in Botanic Garden, Yogi Vemana University, Kadapa, Andhra Pradesh, India - Reddy, A. Madhusudhana; Nagendra, Chennuru (Journal of the Bombay Natural History Society (JBNHS), 2025)
No Abstract.